The Multicultural Education in the Perspective of Islamic Education Philosophy - Lestari, Ade; Salminawati, Salminawati; Usiono, Usiono (Bulletin of Science Education, 2023)
This paper explains that multicultural education emphasizes the importance of respecting and understanding cultural diversity in education. In the context of Islamic education philosophy, multicultural education has a deep relevance and is in line with the basic principles of Islam that emphasize equality, justice, and equality among all humans regardless of race, ethnicity, or cultural background. Islam encourages its people to know and understand each other, in accordance with Allah's words in the Qur'an letter Al-Hujurat verse 13 which mentions the importance of knowing each other. Therefore, multicultural education in the Islamic perspective is not only a necessity in a plural society, but also part of the practice and demands of religion. The multicultural approach in Islamic education helps enrich students' understanding of diversity and teaches them to be tolerant and respectful of differences. Through this education, it is hoped that a harmonious, peaceful and respectful society can be realized in the midst of cultural and religious diversity Keywords: Multicultural Education, Islamic Education Philosophy, Education